2011
DOI: 10.1007/978-3-642-21227-7_48
|View full text |Cite
|
Sign up to set email alerts
|

Fully Automatic Liver Volumetry Using 3D Level Set Segmentation for Differentiated Liver Tissue Types in Multiple Contrast MR Datasets

Abstract: Abstract.Modern epidemiological studies analyze a high amount of magnetic resonance imaging (MRI) data, which requires fully automatic segmentation methods to assist in organ volumetry. We propose a fully automatic two-step 3D level set algorithm for liver segmentation in MRI data that delineates liver tissue on liver probability maps and uses a distance transform based segmentation refinement method to improve segmentation results. MR intensity distributions in test subjects are extracted in a training phase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…information about computing time. Finally, Gloger et al in [16] report tests over datasets of healthy and fatty livers. The runtime analysis was performed on a 1.8 GHz Intel core 2 Duo Processor with 3 GB of RAM, and it ranges from 11.22 ± 2.78 min for healthy livers and 15.37 ± 4.96 min for fatty livers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…information about computing time. Finally, Gloger et al in [16] report tests over datasets of healthy and fatty livers. The runtime analysis was performed on a 1.8 GHz Intel core 2 Duo Processor with 3 GB of RAM, and it ranges from 11.22 ± 2.78 min for healthy livers and 15.37 ± 4.96 min for fatty livers.…”
Section: Discussionmentioning
confidence: 99%
“…Gloger et al develop a fully automatic three-step 3D segmentation approach in MRI based upon a modified region growing methodology and a further thresholding technique [15]. Other approach of same authors can be found in [16] to estimate liver volume. Therein, it is proposed a 3D level set algorithm that delineates liver tissue on liver probability.…”
Section: Introductionmentioning
confidence: 97%
“…So, the results presented in this paper cannot be compared in a direct manner with the results of these authors but initial conclusions can be extracted from this comparison. In the About MRI methods (table 5), in the fully automatic algorithms only healthy patients were used for the method validation (or fat livers in two cases), i.e, patients with tumors were not used [20,9,35,22]. Besides that, two of them used few images for validation [35,22] and other two used only a type of coefficient for the validation procedure [20,9] so a direct comparison with our results is difficult.…”
Section: Datasetmentioning
confidence: 99%
“…The liver segmentation methods found in the state-of-the-art in MRI are based mainly on level-set methods [17,18,19,20,21,22], where the drawbacks of these algorithms (difficult training, high computational cost, or high user iteration) are noticeable. Specially, in [18], a level-set method (a fast marching algorithm) and fuzzy theory are applied in the liver segmentation task, but the computational cost of this algorithm needs to be improved (as the authors themselves recognize) and, additionally, non-uniform intensity problems are not solved.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation